205k views
4 votes
2/5 (z+ 1) = y for z

User Nckturner
by
4.6k points

1 Answer

0 votes

The equation given is


(2)/(5)(z+1)=y

We need to solve for the variable "z".

First, we multiply the term "z + 1" by "2/5" and do a bit algebra to isolate "z".

The steps are shown below:


\begin{gathered} (2)/(5)(z+1)=y \\ (2)/(5)(z)+(2)/(5)(1)=y \\ (2)/(5)z+(2)/(5)=y \\ (2)/(5)z=y-(2)/(5) \\ z=(y-(2)/(5))/((2)/(5)) \end{gathered}

We can simplify this a bit further:


\begin{gathered} z=(y-(2)/(5))/((2)/(5)) \\ z=(y)/((2)/(5))-((2)/(5))/((2)/(5)) \\ z=(5)/(2)y-1 \end{gathered}

User Forien
by
4.6k points